Early detection of sonographic factors for promotion of healthy pregnancy - Rachna Chaurasia; Tushar Agarwal (Asian Journal of Medical Sciences, 2025)
Background: Ultrasonography has revolutionized obstetric care over the past four decades by providing critical information about early pregnancy development and complications. This study focuses on evaluating the role of ultrasound (USG) in detecting embryonic demise and fetal anomalies in early part of pregnancy before targeted imaging for fetal anomalies scan. Aims and Objectives: The primary objective is to assess the sonographic features for early detection of fetal anomalies before 18 weeks of gestation and identify early signs of pregnancy failure or potential complications, enabling timely pregnancy management. Materials and Methods: This observational study was conducted at Maharani Laxmi Bai Medical College, Jhansi, involving pregnant women up to 18-week gestation. Participants underwent routine and targeted USG scans, including color Doppler studies. Data were collected on maternal, embryonic, fetal, and placental variables, and outcomes were monitored through follow-up scans and clinical evaluations. Results: Among 1080 antenatal USG scans, 240 showed abnormal sonographic findings. These were categorized based on gestational age and indications for scans. Notable findings included a higher abortion rate linked to irregular gestational sac borders, enlarged gestational sacs, low implantation, and enlarged yolk sacs. Fetal anomalies such as neural tube defects, anencephaly, and hydrops fetalis had a high correlation with adverse outcomes. Maternal factors, including large fibroids, uterine anomalies, and short cervical canals, were also associated with increased abortion rates. Doppler studies highlighted that a high uterine artery pulsatility index predicted pre-eclampsia and intrauterine growth restriction. Conclusion: Early pregnancy ultrasonography plays a vital role in detecting embryonic demise and fetal anomalies. This study underscores the importance of routine and targeted USG in enhancing pregnancy outcomes through early detection and timely intervention.